2016
DOI: 10.4155/fmc-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

Quinazolinone Azolyl Ethanols: Potential Lead Antimicrobial Agents with Dual Action Modes Targeting Methicillin-Resistant Staphylococcus Aureus DNA

Abstract: Compound 3a should be a potential lead antibacterial molecule with dual action modes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 46 publications
0
20
0
1
Order By: Relevance
“…18,19 Some nonclinical hydroxyethyl azoles have also been developed with superior antibacterial or antifungal potencies. 20,21 These researches clearly demonstrated the enormous potentiality of hydroxyethyl azole in the antimicrobial aspect.…”
mentioning
confidence: 95%
“…18,19 Some nonclinical hydroxyethyl azoles have also been developed with superior antibacterial or antifungal potencies. 20,21 These researches clearly demonstrated the enormous potentiality of hydroxyethyl azole in the antimicrobial aspect.…”
mentioning
confidence: 95%
“…87 Various azolyl ethanol fragments such as imidazolyl, triazolyl, tetrazolyl, benzoimidazolyl, and benzotriazolyl were incorporated at the 3 rd position of quinazolin-4(3H)one by Peng et al to get a series of hybrid analogues as potent antimicrobial agents. 88 These synthesized analogues were screened for in vitro anti-bacterial activity against Gram-positive (Micrococcus luteus ATCC4698, MRSA, Staphylococcus aureus ATCC25923, and Bacillus subtilis ATCC6633) and Gram-negative strains of bacteria (Pseudomonas aeruginosa ATCC27853, Escherichia coli DH52, Bacillus proteus ATCC13315, and Eberthella typhosa ATCC14028). Amongst the synthesized hybrid analogues, triazolyl ethanol hybrids were found to effectively inhibit all the bacterial strains, except for P. aeruginosa, and their activities were comparable or even superior than that of noroxacin (MIC of 8 mg mL À1 ) and chloromycin (MIC of 16 mg mL À1 ) against MRSA.…”
Section: Anti-microbial Hybridsmentioning
confidence: 99%
“…Hybrids 28a,b (MIC: 8.0–16 µg/ml, two‐fold serial dilution technique) were not inferior to chloromycin (MIC: 8.0–32 µg/ml) against Gram‐positive bacteria S. aureus , MRSA, M. luteus , and B. subtilis , and the SAR indicated that the fluoro group was better than the chloro group at the C‐7 position of quinazolinone moiety. [ 72 ] Molecular docking study revealed that hybrid 28a could interact with MRSA DNA by the formation of hydrogen bonds and intercalate into MRSA DNA to form hybrid 28a –DNA complex. Moreover, DNA cleavage properties of hybrid 28a –Cu 2+ and 28a –Zn 2+ complexes were confirmed by agarose gel electrophoresis experiments.…”
Section: Miscellaneous 124‐triazole Hybridsmentioning
confidence: 99%